СВІТОВИЙ ДОСВІД ЗАКОНОДАВЧОГО РЕГУЛЮВАННЯ ЩОДО ЛІТІЙ-ІОННИХ БАТАРЕЙ ЕЛЕКТРОМОБІЛІВ З УРАХУВАННЯМ ЇХ ВТОРИННОГО ЗАСТОСУВАННЯ В ЕНЕРГЕТИЧНОМУ СЕКТОРІ - Kostenko, Ganna; Zaporozhets, Artur (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
Understanding and incorporating global regulatory experiences and standards related to battery management is of greatest importance, particularly when considering the rapid evolution of the electric vehicle (EV) market and its implications for energy storage and sustainability. This is especially relevant for Ukraine, where the burgeoning secondary market for EVs and a keen interest in renewable energy sources underscore the need for proactive policy-making and standardization to address the challenges of battery second life and recycling. This article delves into the role of Electric Vehicle Lithium-Ion batteries within the ambit of the circular economy, underscoring the significance of legislative frameworks across the globe with a particular focus on European initiatives in light of Ukraine's EU integration ambitions. This encompasses extending battery life through recycling and repurposing, thereby ensuring both economic viability and minimal environmental footprint. The narrative outlines the varied legislative landscapes internationally, noting the differences in strategies from Asia's technological and safety emphasis to Europe's robust regulatory directives aimed at battery lifecycle management. In Europe, the drive towards sustainable battery utilization is marked by comprehensive policies like the EU Battery Directive and the emerging Regulation on Batteries and Waste Batteries, which set forth ambitious recycling targets and introduce innovative concepts like the battery passport. Drawing from this global overview, the article posits a set of recommendations for Ukraine, suggesting the development of extensive battery management legislation, adoption of European standards to smooth the path towards EU membership, investment in recycling infrastructures, fostering of public-private partnerships, and public awareness initiatives. These recommendations are designed to elevate Ukraine's position in the sustainability, promoting environmental stewardship and economic competitiveness. The growing importance of secondary lithium-ion batteries for electric vehicles in supporting and harmonizing renewable energy sources is emphasized, and accordingly, the need for adequate legislation and standardization to support a closed-loop economy.